Penerapan Model Pembelajaran Probing Prompting Didukung Multimedia Untuk meningkatkan Hasil Belajar Siswa Di SMA Negeri 2 Tondano - Veibyanti Falensya Dalige; Meiske Mamuaja (Chemistry Department, Universitas Negeri Manado, 2022)
The purpose of this study was to determine student learning outcomes with the application of the probing prompt learning model supported by multimedia, to determine the interaction of students in learning and the relationship between the model and learning media with the material. The research design used is a pre-experimental design where the research uses only one class (experimental class) without any comparison class or control class. Data collection was done by giving a pretest before the learning process was carried out, and a posttest after the learning process. The research data obtained in the form of the difference in the average value of the pretest and posttest, the average value of the pretest is 31.57% and the average value of the posttest is 84.20%. Furthermore, the analysis of learning outcomes on colloidal material also shows an increase, in terms of the N-Gain analysis obtained 0.76 with high criteria and hypothesis testing which shows that t-hitung > t-tabel which means that the probing prompting learning model is supported by multimedia providing improvement of student learning outcomes.